2010
DOI: 10.1103/physrevlett.105.090403
|View full text |Cite
|
Sign up to set email alerts
|

Casimir Repulsion between Metallic Objects in Vacuum

Abstract: We give an example of a geometry in which two metallic objects in vacuum experience a repulsive Casimir force. The geometry consists of an elongated metal particle centered above a metal plate with a hole. We prove that this geometry has a repulsive regime using a symmetry argument and confirm it with numerical calculations for both perfect and realistic metals. The system does not support stable levitation, as the particle is unstable to displacements away from the symmetry axis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
171
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 26 publications
6
171
0
Order By: Relevance
“…Other studies discussing the transition between attractive and repulsive interactions are found in Refs. [16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies discussing the transition between attractive and repulsive interactions are found in Refs. [16][17][18][19].…”
mentioning
confidence: 99%
“…Other studies discussing the transition between attractive and repulsive interactions are found in Refs. [16][17][18][19].Surfaces of interest in biology and biotechnology may involve alkane molecules creating an oil-water interface. In this Brief Report we will demonstrate that the Casimir-Polder interaction between dissolved atoms and different oil-water * mabos@ifm.liu.se † Drew.Parsons@anu.edu.au ‡ bos@ifm.liu.se interfaces may be either repulsive or attractive, or as we will see for some of the alkanes, it may change from repulsion to attraction as the distance to the interface increases.…”
mentioning
confidence: 99%
“…The problem may be resolved if the Casimir force is repulsive [8,12]. Therefore, repulsive Casimir force received unprecedented attention in practical systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…While the conditions for when the Casimir force becomes repulsive are not yet fully understood, several proposals for setups which should yield repulsive Casimir forces have been made. These include setups with conditions of high magnetic permeability [7,8], optical setups involving left-handed metamaterials [9], or non-trivial boundary conditions [10]. Examples of repulsive Casimir forces have been experimentally observed only in recent years [11].…”
Section: Introductionmentioning
confidence: 99%